2014
DOI: 10.1371/journal.pone.0110455
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Promotes DMH-Induced Colorectal Cancer by Increasing the Activity of Glycolytic Enzymes in Rats

Abstract: The objective of the present study was to investigate the association between diabetes mellitus and colorectal carcinogenesis as well as the possible mechanism involved in this interaction. Diabetes rat models were induced with a low dose of STZ followed by a low dose of DMH to induce colorectal cancer. The formation of ACF in the colon and the incidence, number and size of tumors were measured. The activity of glycolytic enzymes in colonic tissues was also measured. The results demonstrated that both the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…In addition to some well‐known pathways related to GDM, we strikingly identified the up‐regulation of several cancer‐related pathways in second‐trimester GDM samples, such as colorectal cancer, cell cycle. It has been widely reported that diabetes could result in elevated colorectal cancer risk (Jarvandi & Davidson, ; Wu et al, ), which was also confirmed in a rat model (Jia et al, ).…”
Section: Discussionmentioning
confidence: 59%
“…In addition to some well‐known pathways related to GDM, we strikingly identified the up‐regulation of several cancer‐related pathways in second‐trimester GDM samples, such as colorectal cancer, cell cycle. It has been widely reported that diabetes could result in elevated colorectal cancer risk (Jarvandi & Davidson, ; Wu et al, ), which was also confirmed in a rat model (Jia et al, ).…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have shown a close link between diabetes and colorectal cancer whereby diabetes could accelerate the incidence of colorectal cancer. The dysfunction of energy metabolism pathways has been implicated in the occurrence and development of colorectal cancer, and the abnormal expression of enzymes involved in glycometabolism might also play an important role in the development of colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…also described an increased incidence of colorectal cancer in a systematic review of 41 cohort studies . Previous studies have shown that the increase of glycolytic enzyme activity promotes colorectal cancer in diabetic rats . In diabetic rats, the activities of HK and PK are increased, whereas Pyruvate dehydrogenase (PDH) activity are decreased.…”
Section: Introductionmentioning
confidence: 97%
“…bacteria such as lipase, amylase, and protease contributed greatly in antioxidant activity [6]. The free radicals generated in the host body cell not only degrade the cellular integrity of the cell but also damage their functionality.…”
Section: Introductionmentioning
confidence: 99%